Design of biomaterials for intracellular delivery of carbon monoxide. (7th August 2015) - Inaba, Hiroshi; Fujita, Kenta; Ueno, Takafumi
Abstract : In this mini-review, current development of biomaterials as carbon monoxide-releasing molecules (CORMs) for intracellular applications is summarized and discussed. Abstract : Carbon monoxide (CO) is recognized as one of the most important gas signaling molecules involved in governing various therapeutic responses. Intracellular generation of CO is spatiotemporally controlled by catalytic reactions of heme oxygenases (HOs). Thus, the ability to control intracellular CO delivery with modulation of the CO-release rate in specific amounts and locations is expected to improve our fundamental understanding of the functions of CO and the development of clinical applications. For this purpose, CO-releasing molecules (CORMs) have been developed and investigated in vitro and in vivo . Most CORMs are based on transition metal carbonyl complexes. Recently, various biomaterials consisting of metal carbonyls with biomacromolecular scaffolds have been reported to improve the properties of bare metal carbonyls. In this mini-review, current progress in CO delivery, recent strategies for the development of CORMs, and future directions in this field are discussed.